2015
DOI: 10.1140/epja/i2015-15152-6
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenology of Pc(4380)+, Pc(4450)+ and related states

Abstract: Abstract. The P c(4380)+ and Pc(4450) + states recently discovered at LHCb have masses close to several relevant thresholds, which suggests they can be described in terms of meson-baryon degrees of freedom. This article explores the phenomenology of these states, and their possible partners, from this point of view. Competing models can be distinguished by the masses of the neutral partners which have yet to be observed, and the existence or otherwise of further partners with different isospin, spin, and parit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(115 citation statements)
references
References 95 publications
(100 reference statements)
3
111
1
Order By: Relevance
“…From the similar results with the Λ 0 b → J=ψK − p and the Λ 0 b → J=ψπ − p decays, seen in the upper panels of Fig. 5, indeed, the two P c states should also be seen in Λ 0 b → J=ψπ − p decays as suggested in the early research [37,38] and found in Ref. [39].…”
Section: The S-/u-channel Contributionssupporting
confidence: 85%
See 1 more Smart Citation
“…From the similar results with the Λ 0 b → J=ψK − p and the Λ 0 b → J=ψπ − p decays, seen in the upper panels of Fig. 5, indeed, the two P c states should also be seen in Λ 0 b → J=ψπ − p decays as suggested in the early research [37,38] and found in Ref. [39].…”
Section: The S-/u-channel Contributionssupporting
confidence: 85%
“…As suggested in Refs. [37,38], LHCb found a new evidence of the observation of these two states by a full amplitude analysis of the Λ 0 b → J=ψpπ − decays [39]. It was remarked before in Ref.…”
Section: Introductionmentioning
confidence: 66%
“…[404] In Ref. [407], Burns studied the model-independent phenomenology of the P c (4380) and P c (4450) pentaquark states based on the meson-baryon molecular configuration. He analyzed possible spin-parity assignments for these two states and speculated various decay patterns and production processes.…”
Section: Other Theoretical Schemesmentioning
confidence: 99%
“…Observations of the same two pentaquark states in another decay would strengthen their interpretation as genuine exotic baryonic states, rather than kinematical effects related to the so called triangle singularity [5,6]. The LHCb collaboration has performed an amplitude analysis of Λ b → J/ψpπ − decays, which are related to Λ b → J/ψpK − decays via Cabibbo suppression [7].…”
Section: Evidence For Exotic Hadron Contributions Tomentioning
confidence: 99%